Does Bilingualism among the Native Born Pay? - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2016)
This paper uses the pooled data from the 2005-2009 American Community Survey to analyze the economic benefits of bilingualism to adult men born in the United States. Bilingualism among the native born is defined as speaking a language at home other than or in addition to English. Native born bilingualism is rare; only 6.5 percent report a non-English language, and of those 71 percent report Spanish. Most of the native born bilinguals report speaking English "very well" (85 percent), with most of the others speaking it "well" (10 percent). Other variables the same, bilinguals earn 4.7 percent less than monolingual English speakers, but the earnings differential varies sharply by the language spoken. Those who speak Native American languages, Pennsylvania Dutch and Yiddish have very low earnings, likely because they live in isolated geographic or cultural enclaves. Those who speak certain Western European and East Asian languages and Hebrew earn significantly more than monolingual English speakers. Spanish speakers earn 20 percent less than the monolingual English speakers overall, but other variables the same, have statistically significant seven percent lower earnings.
Keywords: J24; J31; F22; 330; bilingualism; earnings; native born; linguistic enclaves